Programming basics : getting started with Java, C#,and Python - Ciesla, Robert (Apress, 2021)
Programming Basics offers the fundamentals of what it's like to function in today's world from the perspective of a programmer. The approach is highly practical with numerous small code listings for C#, Java, and Python included. The reigning programming paradigm of object-oriented programming (OOP) is a part of all of these languages and its basics are explained in this book as well. Knowing the basics of coding is beneficial for those working close to, but not quite as one of the programmers in a team of software developers. Many people working in the audiovisual fields in the gaming/media industry would benefit from learning more of the programmers' points of view. The same applies to software testers and even company executives, who might have an education in business instead of computer science. What You'll Learn " Gain a basic understanding of three popular programming languages, namely C#, Java, and Python " Think and read code-listings like a programmer " The basics of Unified Modeling Language (UML) class diagrams " Communicate more efficiently with programmers of all experience levels in a work-based environment " The core concepts related to the object-oriented programming (OOP) " How to set up your programming environments for Windows, MacOS, and Linux Who This Book Is For Those looking to discover programming, including beginners in all fields, and professionals looking to understand how basic coding processes work.